Sofosbuvir and Simeprevir for Treatment of Hepatitis C Virus Infection in Liver Transplant Recipients - Gutierrez, Julio A. (Liver Transpl, 2015)
Recurrent hepatitis C virus (HCV) infection occurs universally in the allograft in the absence of effective antiviral therapy before liver transplantation (LT). Antiviral therapy with sofosbuvir and simeprevir has proven to be highly effective and well tolerated in the nontransplant setting for treatment of HCV genotype 1 infection; therefore, we sought to evaluate the efficacy and safety of this regimen in LT recipients with recurrent HCV infection. This was a retrospective analysis of a single-center treatment protocol of patients with HCV genotype 1 infection who received a 12-week combination regimen of sofosbuvir and simeprevir. Sixty-one patients (35 with genotype 1a and 26 with genotype 1b) completed treatment with simeprevir and sofosbuvir. Three patients received additional ribavirin. Laboratory data and clinical assessments performed at the baseline, on treatment, at the end of treatment, and 12 weeks after the completion of antiviral therapy [sustained virological response at 12 weeks (SVR12)] were analyzed. The median time after LT was 5.4 years [interquartile range (IQR), 1.9-8.4 years], and tacrolimus was the most commonly used immunosuppressive agent (80.3%). Overall, SVR12 was achieved in 93.4% [95% confidence interval (CI), 84%-97%] of LT recipients treated with 12 weeks of sofosbuvir and simeprevir. When they were analyzed according to the HCV subtype, LT recipients with genotype 1b had a 100% SVR12 rate (95% CI, 87%-100%), whereas SVR12 was 89% (95% CI, 74%-95%) for those with genotype 1a. Advanced fibrosis (METAVIR F3-F4) was associated with diminished antiviral efficacy in LT recipients with genotype 1a [SVR12, 67% (95% CI, 39%-86%); P 5 0.01]. Overall, the incidence of adverse events (AEs) was low, and no severe AEs occurred during treatment. In conclusion, treatment with a 12-week regimen of sofosbuvir and simeprevir was well tolerated and resulted in a high SVR12 rate for LT recipients with recurrent HCV genotype 1 infection. Genotype 1a patients with advanced fibrosis of the allograft were more likely to relapse.